Sosialisasi Peran Infrastruktur dalam meningkatkan Kualitas Hidup Masyarakat di Balai Perkumpulan Sub PPKBD Tambakkemerakan, Krian - Wahyu Aldino Saputra (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to enhance public understanding of the role of infrastructure in supporting quality of life, particularly through the utilization of the Sub PPKBD Tambakkemerakan Community Hall in Krian as a social and educational space. The method used is Participatory Action Research (PAR), which emphasizes active community involvement in every stage of the activity, from problem identification to program implementation. The activities were carried out through a series of events that combined elements of togetherness, religiosity, and education, such as communal iftar (breaking the fast), congregational prayers, and an offline webinar featuring student speakers.The results indicate an improvement in community understanding of the importance of utilizing social infrastructure not only as a gathering place but also as a medium for learning and empowerment. In addition, the activity strengthened social interaction, increased community solidarity, and encouraged active participation in utilizing available facilities more productively. Despite several challenges, such as time constraints and differences in participants’ levels of understanding, the activity overall had a positive impact in promoting the optimization of social infrastructure functions. Therefore, the continuation of similar programs is necessary to support sustainable improvements in community quality of life.